(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the effectiveness and significance of the acmeological approach in the training of pre-conscription military training, improving their knowledge and qualifications, preparing for professional activity. At the same time, the task of the acmeological approach in the framework of pedagogical science, its methodology in personnel training is analyzed.